Combination of amniotic epithelial cells with NDGA promotes the survival of transplanted AECs in spinal cord-injured rats. (November 2015) - Zhang, Xiuying; Xue, Hui; Liu, Jiamei; Song, Yu; Zhang, Jiwei; Peng, Ru; Chen, Dong
<x content-type="archive" xml:space="preserve">Abstract</x> Our previous research has shown that seeding amniotic epithelial cells (AECs) in chemically extracted acellular muscle scaffold (CEAMC) better promotes the functional recovery of spinal cord injury (SCI) than scaffold alone. However, the massive death of transplanted cells, which is related to early inflammatory response, is still a problem in cell therapy. Our previous study proved that nordihydroguaiaretic acid (NDGA) inhibits inflammation after SCI. In this study, we tested a strategy of combining the early administration of NDGA and the transplantation of AEC-seeded CEAMC to treat SCI. The results showed that simply increasing the number of surviving AECs had no significant benefits in SCI therapy, but NDGA administration ameliorated transplanted AEC survival demonstrating the potential value of NDGA in the cellular transplantation treatment of SCI.